Leveraging social norms for sustainable behaviour: How the exposure to static-and-dynamic-norm communications encourage sustainable behaviour towards reduction of fashion consumption. - Granato, Giulia; Mugge, Ruth (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
Communication channels from social media to newspapers abound with examples where static norms, reflecting established behaviours (e.g., eating meat, drinking alcohol at parties) are combined with dynamic norms, illustrating emerging societal trends (e.g., adopting more plant-based diets, attending alcohol-free events). Despite widespread exposure to these combined static-and-dynamic-norm communications, their impact on consumer behaviour remains unexplored. Through two lab experiments, this research investigates how static-and-dynamic-norm communications influence sustainable behaviour towards a reduction of fast fashion consumption. Our findings show that consumers exposed to the combination of unsustainable static and unsustainable dynamic norm purchased significantly fewer fashion items compared to other experimental conditions. This effect is driven by social moral cleansing, as consumers, confronted with widespread unsustainable behaviour of others, felt a highlighted motivation to clean and compensate for the normalized bad behaviour of others by behaving more sustainably in return. This research advances the understanding of social normative influences on sustainable consumption and offers valuable insights for researchers, designers and policy makers. By identifying an effective social norm communication to encourage consumption reduction, it lays the groundwork for future research and policy initiatives aimed at promoting sufficiency in the context of sustainable behavioural change.